2015
DOI: 10.1093/rpd/ncv310
|View full text |Cite
|
Sign up to set email alerts
|

Doses Metrics and Patient Age in Ct

Abstract: The aim of this study was to investigate how effective dose and size-specific dose estimate (SSDE) change with patient age (size) for routine head and abdominal/pelvic CT examinations. Heads and abdomens of patients were modelled as a mass-equivalent cylinder of water corresponding to the patient 'effective diameter'. Head CT scans were performed at CTDIvol(S) of 40 mGy, and abdominal CT scans were performed at CTDIvol(L) of 10 mGy. Values of SSDE were obtained using conversion factors in AAPM Task Group Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…However, their spatial resolution is limited by that of the PET modality, and is on the order of 5–10mm, limiting any anatomy-specific information available in the image. PET imaging also requires the use of radio-isotopes, and carries the risk of significant radiation: an amyloid PET scan is estimated to expose the patient to about 7mSv [1] of radiation dose, roughly equivalent to several CT scans (a typical head CT in an adult is about 2mSv [2]). Global distribution of the PET agents also remains a challenge due to their short half-life.…”
Section: Introductionmentioning
confidence: 99%
“…However, their spatial resolution is limited by that of the PET modality, and is on the order of 5–10mm, limiting any anatomy-specific information available in the image. PET imaging also requires the use of radio-isotopes, and carries the risk of significant radiation: an amyloid PET scan is estimated to expose the patient to about 7mSv [1] of radiation dose, roughly equivalent to several CT scans (a typical head CT in an adult is about 2mSv [2]). Global distribution of the PET agents also remains a challenge due to their short half-life.…”
Section: Introductionmentioning
confidence: 99%
“…Because age is an easily obtainable factor, the correlation between age and d w was also assessed to determine whether age can be used as a d w surrogate to estimate SSDEs. Unfortunately, unlike [28], no significant correlation was observed between d w and age for chest and abdomen-pelvis CT, which is attributed to the lack of growth of d w with the increasing ages of adult patients. However, similar to previous results reported by Menke [20,25], we also found that both body weight and BMI strongly correlated with d w in chest and abdomen-pelvis, despite different populations in Asian-Pacific and European-American regions.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the number of obese patients at our hospital is very small, and the effective dose calculated using SSDE was higher than that determined via the conventional method using CTDI vol alone in all cases (DLP). Given these results, when estimating the organ dose and effective dose for pediatric patients and the standard and thin body type patients, the SSDE-corrected value is less likely to underestimate the exposure dose than the conventional method using CTDI vol and DLP, making SSDE a very effective method [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%